PRESCHOOL EDUCATION IS THE FOUNDATION OF A CHILD'S DEVELOPMENT (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Caring about the future generation, striving to bring up a healthy, well-rounded generation, strengthening our national values passed down from time to time, from generation to generation. Also, to inculcate the ideas of Humanity-oriented education. It is stated that every parent struggles throughout his life to see the happiness and perfection of his child, and that children who grow up in such a family value national traditions, values, and customs.